Quality Control Analysis of Sickle Products Using Statistical Quality Control (SQC) and Failure Mode and Effects Analysis (FMEA) - Fatikhul Arief; Moh. Jufriyanto (G-Tech: Jurnal Teknologi Terapan, 2025)
PT. ABC is a manufacturing company that produces agricultural and plantation tools, with one of its superior products being sickles. The main problem faced by the company lies in the high number of defective products in sickle, so this study was conducted with the aim of minimizing defects in these products. This study applied the Statistical Quality Control (SQC) method as a quality management approach to control product quality through the integration of the Failure Mode and Effect Analysis (FMEA) and SQC methods. Primary data was obtained through interviews to identify the causes of product defects, while secondary data was obtained from production reports and the company's defect count. Based on the results of the analysis using a pareto diagram, it was found that 88% of quality problems were caused by cracks in the sickle blades. Furthermore, through Risk Priority Number (RPN) analysis, it was found that the main contributing factor was human error, namely operators who did not understand the applicable standard operating procedures (SOP), with an RPN value of 315. This finding indicates that crack defects are a dominant factor affecting product quality.